Resposta :
a) 3x + 4 - 2x = 10 - 4x + 9
x + 4 = 19 - 4x (coloquei os termos similares em evidência)
x + 4x = 19 - 4
5x = 15
x = 15/5
x = 3
b) 6x - 3 = 4x + 6
6x - 4x = 6 + 3
2x = 9
x = [tex]\frac{9}{2}[/tex]
c) 3 - 2x = - 5x - 9
- 2x + 5x = - 9 - 3
3x = - 12
x = - 12/3
x = - 4
d) 7x + 4 - 2x = 3x - 10
5x + 4 = 3x - 10
5x - 3x = - 10 - 4
2x = - 14
x = - 14/2
x = - 7
e) 4x + 5x = 10 + 5
9x = 15
x = 15/9
x = [tex]\frac{5}{3}[/tex]
f) 2x + 5 = - 5x + 4
2x + 5x = 4 - 5
7x = - 1
x = [tex]-\frac{1}{7}[/tex]
Espero que tenha ajudado .-.